Hubungan Game Online dengan Kemampuan Berpikir Kritis Matematis Siswa Kelas VIII SMP - Imamuddin, M.; Fitri, Haida; Rahmadila, Rahmadila (Institut Agama Islam Negeri (IAIN) Tulungagung, 2019)
This research was motivated by author's observation at SMP N 1 Ampek Angkek where some of the students was a game players. Although they were played game online, they still got good grades in their school.This study aims to determine the relationship of online games with students' mathematical critical thinking skills held at SMP N 1 Ampek Angkek. This research is a quantitative research with the type of research used is relationship research. The independent variable in this study is online games and the dependent variable is students' critical thinking abilities. The population in this study amounted to 114 students, while the sampling was done by random sampling of 29 students. Based on the results of the research that the researchers did obtained the value of the Pearson Product Moment relationship, r(count) = 0.068 with 0.05 significance level. So that based on the interpretation of the coefficient relationship r value is between 0.00 <0.068 <0.199, the relationship between the two variables (online games with critical thinking skills) is very low. Based on the significance test obtained sig = 0.728. Because the value of sig = 0.728> α = 0.05, it can be concluded that there is correlationship but not significant between online games with mathematical critical thinking skills at SMP N 1 Ampek Angkek.